2006
DOI: 10.1111/j.1525-1438.2006.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of [18F]fluoro-2-deoxy-D-glucose positron emission tomography in re-recurrent cervical cancer

Abstract: Cervical cancer patients with histologically documented re-recurrence after curative salvage therapy or unexplained tumor marker elevation (negative computed tomography and/or magnetic resonance imaging [CT-MRI]) proven to be a re-recurrence when a further attempt for cure (or control of cancer) appeared feasible were enrolled. Lesion status was determined from pathology or clinical follow-up for at least 12 months. Management decisions were recorded with CT-MRI alone and incorporating [18F]fluoro-2-deoxy-D-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The use of FDG-PET which has shown superior ability to CT/MRI in detecting nodal, distant soft tissue metastasis lesion and more accurately detecting the presence and location of cancer cell, helps clinicians in selecting appropriate and individualized patients for curative salvage treatment [17,18]. In selected cases such as supraclavicular or para-aortic nodal metastasis detected by FDG-PET and where more aggressive curative salvage therapy after recurrence e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The use of FDG-PET which has shown superior ability to CT/MRI in detecting nodal, distant soft tissue metastasis lesion and more accurately detecting the presence and location of cancer cell, helps clinicians in selecting appropriate and individualized patients for curative salvage treatment [17,18]. In selected cases such as supraclavicular or para-aortic nodal metastasis detected by FDG-PET and where more aggressive curative salvage therapy after recurrence e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of FDG-PET exceed those of CT-MRI mainly because of the ability of FDG-PET to identify extra-pelvic metastases and its higher sensitivity and specificity [56]. Overall FDG-PET has a positive impact on 46% patients in cervical cancer patients with histologically documented rerecurrence after curative salvage therapy or unexplained tumor marker elevation [57].…”
Section: Response Evaluation Surveillance and The Management Of Recmentioning
confidence: 98%
“…21 PET and integrated PET/CT are valuable tools for assessing prognosis 22e24 and primary staging, 23e32 the determination of the treatment goal (curative or palliative) in patients with PALN 31 or SLN 32 metastasis as detected by CT/MRI (Table 1 23e32 ) and the treatment response after the completion of concurrent chemoradiation, 33 and documenting recurrent cervical cancer, 34 unexplained posttreatment elevations in tumor markers, 35 and follow-up after salvage therapy. 36 An early study demonstrated the significant sensitivity of PET for detecting PLN metastasis over MRI. 37 Goyal et al reported that using PET/CT alone could avoid multimodality therapy for the treatment of operable stage IB1eIIA1 cervical cancer.…”
Section: Recent Advances In Molecular Imaging Technologies Pet Imagingmentioning
confidence: 99%